2014
DOI: 10.1210/jc.2013-4064
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Apparently Nonfunctioning Adrenal Incidentalomas May Be at Increased Cardiovascular Risk Due to Excessive Cortisol Secretion

Abstract: Patients with CSAI without hypertension, diabetes, and/or dyslipidemia exhibit adverse metabolic and CVR factors. In addition, NFAIs are apparently associated with increased insulin resistance and endothelial dysfunction that correlate with subtle but not autonomous cortisol excess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 42 publications
6
98
0
2
Order By: Relevance
“…There was no difference in terms of insulin sensitivity between the two groups of adrenal lesion patients, but subjects with sCS had a significantly higher prevalence of IGT and a higher area under the curve for glucose (19). These data and other studies demonstrate that patients with adrenal incidentaloma, regardless of the functional status, show insulin resistance (20,21,22,23). Moreover, one study found a correlation between adrenal lesion size and insulin resistance (20).…”
Section: Gcs and Glucose Metabolismsupporting
confidence: 54%
See 1 more Smart Citation
“…There was no difference in terms of insulin sensitivity between the two groups of adrenal lesion patients, but subjects with sCS had a significantly higher prevalence of IGT and a higher area under the curve for glucose (19). These data and other studies demonstrate that patients with adrenal incidentaloma, regardless of the functional status, show insulin resistance (20,21,22,23). Moreover, one study found a correlation between adrenal lesion size and insulin resistance (20).…”
Section: Gcs and Glucose Metabolismsupporting
confidence: 54%
“…Therefore, we could turn the question around and ask whether insulin, a known growth factor, might have a potential role in the development and growth of the adrenal lesions (20). On the other hand, patients with non-functioning adrenal lesions could develop insulin resistance because of a subtle alteration of cortisol secretion dynamics not identifiable as autonomous sCS (22).…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 99%
“…In total, 12 studies were included: 7 cross-sectional studies (38,42,43,45,141,142,143) and 5 cohort studies (40,46,144,145,146). In eight studies, a comparison was made between patients with elevated (group 1) or normal (group 2) cortisol levels after a 1 mg dexamethasone test.…”
Section: Assessment Of Autonomous Cortisol Secretion In Relation To Cmentioning
confidence: 99%
“…Despite the frequency of mild cortisol-secreting adenomas (1,5) and their association with cardiovascular risk and metabolic derangements (3), there remains a lack of consensus regarding formal diagnostic criteria and treatment recommendations for this condition. Furthermore, recent studies showed that patients with "nonfunctional" (post-DST cortisol ≤1.8 µg/dL) adrenal adenomas present with insulin resistance, increased carotid intima medial thickness, and impaired vascular flow, and are at increased risk of developing diabetes (6,7). This raises the question of whether "nonfunctional" adrenal adenomas are truly nonfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…Post-dexamethasone suppression test (DST) serum cortisol values >1.8 µg/dL are considered "possible" autonomous cortisol secretion, and additional testing, including adrenocorticotropic hormone (ACTH), may be indicated to confirm hypercortisolism (5). While cortisol values ≤1.8 µg/dL are thought to exclude autonomous cortisol secretion (5), a growing number of studies have demonstrated increased cardiovascular risk, impaired glucose tolerance, diabetes, and hypertension in patients with "nonfunctional" adrenal adenomas based on this cutoff (6,7). Presented here are two patients with adrenal adenomas whose cases further question the definition of clinically relevant cortisol secretory activity.…”
Section: Introductionmentioning
confidence: 99%